A MARXIST READING OF MARGARET ATWOOD’S THE HANDMAID’S TALE - TURKI, Harith; Abdulrazzaq, Dulfqar (Al-Adab Journal, 2023)
Margaret Atwood’s The Handmaid’s Tale is a salient dystopian fiction considered as an allusion to the reader’s reality, where it highlights a futuristic totalitarian regime in which people are dehumanized and live in horror and indignity. However, the purpose of this article is to explore the class conflict between the various women’s social classes under the Gileadean regime and its resulting persecution. Moreover, this study adopts Marxist Feminism as a theoretical framework to read the text and explore the implications of social class conflicts and clashes among women in the household. Consequently, the current paper reached the following findings: First, the Gileadean regime deliberately creates differences among the women in the household in order to exploit them and creates a state of conflict among themselves. Second, the regime fabricated a false consciousness among each class, especially the Handmaids, to deceive them and make them think they are superior in society in order to keep them under control so as to be used as sacred vessels or fertile reproduction machines for the infertile women of high class. Finally, Gilead was able to make women turn on each other as the upper class of women played the role of patriarchy in persecuting the inferior classes of women.